2020
DOI: 10.1002/er.5918
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on2Dphotoelectric emission ofGaNnanorod array and nanocone array photocathode

Abstract: Summary In order to improve the photoemission performance of gallium nitride (GaN) ultraviolet vacuum photoelectric devices and to obtain GaN photocathode with high quantum efficiency in this paper. The photoelectric emission theoretical models of GaN nanorod array and GaN nanocone array are constructed, and the models are simulated by COMSOL Multiphysics and MATLAB software. By changing the structure of the photocathode emission layer, the low photoemission performance of the conventional reflection‐mode thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The introduction of a thin graphene sheet could also reduce the high lattice mismatch between GaN and other substrates, such as the widely used Al 2 O 3 or Si. The cut-off spectral response for p-GaN photocathodes is usually at 360 nm 156 and thus a little relief of the UV-laser system can be guaranteed. However, the spectral response is adjustable by the manipulation of the E gap with suitable dopant atoms.…”
Section: Gallium Nitridementioning
confidence: 99%
“…The introduction of a thin graphene sheet could also reduce the high lattice mismatch between GaN and other substrates, such as the widely used Al 2 O 3 or Si. The cut-off spectral response for p-GaN photocathodes is usually at 360 nm 156 and thus a little relief of the UV-laser system can be guaranteed. However, the spectral response is adjustable by the manipulation of the E gap with suitable dopant atoms.…”
Section: Gallium Nitridementioning
confidence: 99%
“…In order to absorb solar energy as high as possible, nanostructures of different shapes have been continuously developed. More and more research results have shown that InGaN nanostructures can achieve higher incident light absorption through antireflection. These are mainly attributed to the trapping effect of nanostructures. , Zhangyang et al used first-principles to calculate the electrical and optical properties of InGaN NWA structures under different In components.…”
Section: Introductionmentioning
confidence: 99%